Antiproliferative activity and antioxidative potential of Swiss chard from Montenegro, grown under different irrigation and fertilization regimes. Issue 7 (24th February 2021) - Ivanović, Ljubica; Topalović, Ana; Bogdanović, Višnja; Đurović, Dijana; Mugoša, Boban; Jadranin, Milka; Tešević, Vele; Beškoski, Vladimir
Abstract : Purpose: The purpose of this paper is to determine the polyphenol content, antioxidative potential and antiproliferative activity of Swiss chard from Montenegro, grown under different irrigation and fertilization regimes. Design/methodology/approach: Swiss chard was grown in the open field (Lješkopolje, Montenegro) where it was subjected to different fertilization and irrigation regimes. Chard samples were analyzed for previously identified polyphenols and for antioxidant parameters. Additionally, in order to complete the biological activities, chard extracts were tested for antiproliferative activity against MFC-7 and HT-29 tumor cell lines. Findings: The polyphenols identified in Swiss chard were flavonoids: vitexin-2?-O-xyloside, vitexin-6?-O-acetyl-2?-O-xyloside, vitexin-6?-O-malonyl-2?-O-xyloside and isorhamnetin-3, 7-diglucoside. In the antioxidant tests, DPPH (2, 2-diphenyl-1-picrylhydrazyl), and ABTS (2, 2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)), chard extract had values of 7.00 and 8.50 (mean values) µmol Trolox (6-hydroxy-2, 5, 7, 8-tetramethylchroman-2-carboxylic acid) equ/d.w., respectively. The tested chard extracts inhibited cell proliferation at different concentrations (3.125–50.0 µg/mL) against the MCF-7 cell line, after 24 and 48 h of incubation. The antiproliferative activity, expressed in terms of IC50, was 32.97 and 86.45 µg/mL after 24 h of incubation and 20.76 and 23.33 µg/mL after 48 h of incubation, for treated and untreated chard extracts, respectively. Originality/value: These data suggest Montenegrin Swiss chard grown under different irrigation and fertilization treatments can be considered as a functional food and should be included in an everyday diet. The collected data could help in the growth improvement of chard with functional food properties.